2022
DOI: 10.1038/s41598-022-18545-6
|View full text |Cite
|
Sign up to set email alerts
|

Topical pharmacotherapy for ocular surface squamous neoplasia: systematic review and meta-analysis

Abstract: Ocular surface squamous neoplasia (OSSN) has different treatment modalities. Although surgical excision has been the gold standard therapeutic option, topical pharmacotherapy agents such as 5-fluorouracil (5-FU), interferon alfa-2b (IFN) and mitomycin-C (MMC) are also commonly used. The protocol was registered (CRD42021224961). Comprehensive literature research was carried out to compare topical pharmacotherapy (5-FU or IFN or MMC) to surgical excision regarding clinical success (tumor resolution), recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Topical chemotherapeutic agents of MMC, 5-FU, and IFNα-2b demonstrate no significant clinical benefit on tumor resolution (overall risk [OR]: 0.785; 95% confidence interval, 0.130–4.736, P = 0.792) or tumor recurrence (OR: 0.746; 95% confidence interval, 0.213–2.609, P = 0.646) over surgery alone. 4 Nanji et al 5 reported that the recurrence rate after IFNα-2b therapy (topical or intralesional injections) was 3% at 1 year and 25% at 5 years, while it was 5% at 1 year and 11% at 5 years after surgical excision. There was no statistical difference between 2 groups ( P = 0.8).…”
Section: Discussionmentioning
confidence: 99%
“…Topical chemotherapeutic agents of MMC, 5-FU, and IFNα-2b demonstrate no significant clinical benefit on tumor resolution (overall risk [OR]: 0.785; 95% confidence interval, 0.130–4.736, P = 0.792) or tumor recurrence (OR: 0.746; 95% confidence interval, 0.213–2.609, P = 0.646) over surgery alone. 4 Nanji et al 5 reported that the recurrence rate after IFNα-2b therapy (topical or intralesional injections) was 3% at 1 year and 25% at 5 years, while it was 5% at 1 year and 11% at 5 years after surgical excision. There was no statistical difference between 2 groups ( P = 0.8).…”
Section: Discussionmentioning
confidence: 99%
“…The variability in OSSN presentation can result in overlooked or misdiagnosed cases, emphasizing the need for meticulous evaluation of any unusual ocular surface abnormality [ 12 , 13 ]. Therefore, incorporating OSSN into the differential diagnosis of every conjunctival mass, especially when accompanied by supporting risk factors such as: smoking, ultraviolet light exposure, human papilloma virus, xeroderma pigmentosa, and immunosuppression, is crucial for early detection and prompt intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the consensus regarding rst-line therapy for OSSN has transformed from surgical excision towards topical pharmacotherapy 7,8 . Topical medications focusing on interferon-α2b (IFNα2b) and 5uorouracil (5-FU) gain reputation as an effective alternative for treating microinvasive tumors diffusedly and promoting tumor resolution on target [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%